A Spectroscopic Method for Hydroxyl Value Determination of Polyols. (4th September 2013) - Chalasani, Siva Rama Krishna; Dewasthale, Sudhanwa; Hablot, Elodie; Shi, Xiangke; Graiver, Daniel; Narayan, Ramani
Abstract: A relatively simple method is described for routine determination of hydroxyl values for a wide range of hydroxyl containing compounds including soybean oil polyols, polyols derived from soy meal, polyether polyols and ethylene glycol as well as their blends. This method is based on reacting the hydroxyl compound with hexamethyldisilazane (HMDS) and determining the FTIR peak area of the silylated product at 1, 251 cm −1 . The method is simple, accurate and reproducible. It is not limited to a specific family of polyol compounds. It does not require any special equipment, hazardous chemicals and can be carried out by non‐technical staff as a rapid and convenient method for quantitative determination of hydroxyl values. An excellent linear correlation was obtained between this spectroscopic method and conventional titration methods for different polyols over a wide range of hydroxyl values. Furthermore, unlike the titration methods the current method is not affected by the presence of acid, base or small amounts of water in the test sample.